An exploratory study demonstrating the diagnostic ability of healthcare professionals in primary care using online case studies for common skin conditions. (5th June 2013) - Tucker, Rod; Patel, Mahendra; Layton, Alison L; Walton, Shernaz
Abstract: Objectives: To compare the diagnostic ability of pharmacists, nurses and general practitioners (GPs) for a range of skin conditions. Methods: An online study comprising 10 specifically developed dermatological case studies containing a digital image of the skin condition and a short case history. A total of 60 participants (20 representing each of pharmacists, GPs and primary care nurses) were required to identify the skin condition as well as the features in the case history that supported the diagnosis and the recommended first-line management approach for the condition. Key findings: The mean diagnostic scores for each group were GPs = 8.8 (95% confidence interval, CI, 7.9–9.6), pharmacists = 6.2 (95% CI, 5.4–6.9) and nurses = 7.0 (95% CI, 6.1–7.9). Post hoc analysis revealed that the difference in mean diagnostic scores was significant ( P < 0.05) between GPs and both pharmacists and nurses. However, pharmacists' diagnostic accuracy was similar to GPs' for some skin conditions such as tinea corporis, scabies and plantar warts and overall at least 40% of pharmacists correctly identified all conditions. Conclusion: This small study has demonstrated that for all of the skin conditions considered, pharmacists' overall diagnostic scores were significantly different from those of GPs but similar to those of nurses for the conditions assessed. However, further work with a larger sample is required to determine the accuracy of these preliminary findings and to establish whether advice given by pharmacists in practice results in the appropriate course of action being taken.